2013
DOI: 10.1007/s00264-013-1917-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction with LARS™ artificial ligament results at a mean follow-up of eight years

Abstract: Purpose The aim of this study was to review patients that underwent ACL reconstruction with the LARS™ ligament in the First Orthopaedic Division of Pisa University during the period between January 2003 and December 2005. Methods Twenty-six patients were reviewed with an average follow-up of 95.3 months (7.9 years). The review protocol was articulated in three phases: (1) a subjective evaluation using three grading scales: VAS, KOOS and the Cincinnati knee rating scale, (2) a clinical and objective evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 25 publications
1
57
0
1
Order By: Relevance
“…Artificial ligaments became highly attractive for orthopaedic surgeons at that time due to the lack of donor side morbidity and the ability of early return to sport activities [2]. Accelerated rehabilitation, immediate knee stability and full weight bearing following surgery were feasible compared to biological grafts [3] thus leading to encouraging results in the short-term [4,5]. Despite the initial enthusiasm, clinical research revealed a high percentage of complications in the long-term such as mechanical failures (prosthetic components breakage, fixation loss), synovial complications (foreign body synovitis), chronic effusions, recurrent instability and early knee osteoarthritis [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial ligaments became highly attractive for orthopaedic surgeons at that time due to the lack of donor side morbidity and the ability of early return to sport activities [2]. Accelerated rehabilitation, immediate knee stability and full weight bearing following surgery were feasible compared to biological grafts [3] thus leading to encouraging results in the short-term [4,5]. Despite the initial enthusiasm, clinical research revealed a high percentage of complications in the long-term such as mechanical failures (prosthetic components breakage, fixation loss), synovial complications (foreign body synovitis), chronic effusions, recurrent instability and early knee osteoarthritis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of artificial ligaments has been discussed critically in the literature [7,9], LARS™ ligaments (Ligament Advanced Reinforcement System, Surgical Implants and Devices, Arc-sur-Tille, France) has been reported to be a suitable material for ACL reconstruction [3,5,[9][10][11][12]. As if history would repeat itself, clinical results in the long-term are again lacking in the literature to confirm the safety and effectiveness of the LARS™ system as a suitable graft for the reconstruction of the ACL.…”
Section: Introductionmentioning
confidence: 99%
“…And the longitudinal fibers are parallel and pre-twisted at 90°. [26] According to the number of longitudinal fibers, the diameter of the ligament has different sizes and they are used for different situations.…”
Section: Artificial Ligamentmentioning
confidence: 99%
“…47 Also, a follow-up at a mean of 8 years reported by Parchi et al in 2013 showed satisfying results reflected in no postoperative complication occurrence and only one case of LARS rupture. 49 On the other hand, the follow-up of 10 years postoperatively carried out by Tiefenboeck et al (2015) revealed lack of subjective satisfaction in half of patients treated with the use of LARS, thus the authors suggested not to consider the ligament system as a potential graft for primary reconstruction of the ACL and rather treat it as an alternative graft in special cases.…”
Section: Ligament Advanced Reinforcement System (Lars)mentioning
confidence: 99%